Current Trends in Unilateral Cleft Lip Care: A 10-Year Update on Practice Patterns. Issue 5 (May 2020) - Roberts, John M.; Jacobs, Aaron; Morrow, Brad; Hauck, Randy; Samson, Thomas D.
Abstract : Background: The care of unilateral cleft lip (UCL) patients is extremely variable. Historical benchmarks for perioperative and intraoperative choices by cleft surgeons were produced by Sitzman et al ( Plast Reconstr Surg. 2008;121:261e–270e) in 2005. However, emerging data and cleft lip repair methods around this period were not captured by this study. The aim of this study was to update the current practice patterns of cleft lip surgeons. Methods: An electronic survey was distributed to surgeons in the American Cleft Palate Association. Demographic data about the surgeon were collected as well as their choices regarding perioperative and intraoperative cleft lip care. Results: Eighty-six surgeons responded to the survey. Nearly 40% of surgeons have changed their technique for UCL repair with Fisher anatomical subunit repair gaining significant popularity. Nasoalveolar molding is also being used more frequently (41% vs 22%). At the time of the cleft lip repair, closure of the nasal floor is occurring in 83.1% of patients and primary cleft rhinoplasty is being performed routinely 57% of the time. Conclusions: Over the last 10 years, there has been an increase in the use of modified rotation advancement repairs and Fisher anatomic subunit approximation technique for treatment of UCL. There continues to be a lack of evidence regarding superiority of specific repair techniques or the benefits of adjunct procedures, which results in varying practice patterns. Educating all cleft surgeons on practices that are well supported is important to improve care to cleft patients.